Histone Deacetylase 4 Promotes Osteosarcoma Cell Proliferation and Invasion by Regulating Expression of Proliferating Cell Nuclear Antigen - Cao, Kun; Wang, Hao; Fang, Yueyang; Wang, Yuan; Wei, Lei; Chen, Xi; Jiang, Zheng; Wei, Xiaochun; Hu, Yong (Frontiers in Oncology, 2019)
Background/Aims: Osteosarcoma (OS) is commonly characterized by lower survival rates and high incidences of local recurrence due to its highly aggressive nature and metastatic tendencies. Studies have shown that histone deacetylase 4 (HDAC4) and proliferating cell nuclear antigen (PCNA) are highly expressed in cancers. Nevertheless, the roles of HDAC4 and PCNA in osteosarcoma (OS) remain unclear. This research aimed to study the expression of HDAC4 and PCNA and their relation to cell proliferation and invasion in human OS. Methods: The levels of HDAC4 and PCNA mRNA and protein were tested in human OS and osteochondroma (OC) tissues. The overexpression and knockdown of HDAC4 in OS cell lines were used to determine the effect of HDAC4 on the expression and degradation of PCNA. The effect of HDAC4 on cell proliferation, invasion and apoptosis was also detected. Additionally, we explored the interaction between HDAC4 and PCNA. Results: The results showed that both HDAC4 and PCNA were increased in human OS tissues. Overexpression of the HDAC4 protein increased the protein level of PCNA, had no effect on the PCNA mRNA level, and decreased the level of ubiquitinated PCNA. We found that overexpression of HDAC4 promoted cell proliferation and invasion and inhibited apoptosis. The opposite effects were observed when HDAC4 was knocked down. The results also showed that HDAC4 could bind to PCNA directly. Conclusions: Our findings suggest that HDAC4 could promote OS cell proliferation and invasion by regulating the expression of PCNA. Thus, our research indicates that HDAC4 may be a potential target for therapy in OS.